Effect of different tool flank wear lengths on the deformations of an elastic cutting tool and the machined workpiece. (16th January 2006) - Lin, Zone-Ching; Lo, Ship-Peng
To understand the effects of tool elastic deformation generated by high normal stresses during metal cutting processing and artificial tool flank wear on the cutting process, an iteration mathematical model for calculating the tool-workpiece contact problem was developed in this paper under the assumption of elastic cutting tools. In this model, the finite element method is used to simulate cutting of mild steel by the P20 cutting tool with three different lengths of artificial tool flank wear. The results obtained in the simulation were found to match the experimental data reported by related studies. The simulation results also indicate that the thrust and the cutting forces are a function of the length of artificial flank wear land. The temperature distribution on the tool flank wear increases with the increase in tool flank wear length. Besides, the normal stress on the wear land generally decreases with the increase in tool flank wear. Factors affecting the tool rake face and tool flank deformation are all derived from the interactions between the normal stress and temperature distribution. The crater deformation on the tool rake face occurs because of the greater effect of normal stress than that of temperature distribution. On the contrary, the convex deformation on the tool flank is formed because the effect of the temperature distribution is greater than that of normal stress.